A STUDY ON THE ROLE OF ARTIFICIAL INTELLIGENCE, AUTOMATION AND DATA EDUCATION IN THE MODERN ERA (International Journal of Food and Nutritional Sciences, 2023)
In the rapidly advancing digital world, Artificial Intelligence (AI), automation and data education have emerged as transformative forces. These elements influence sectors such as education, industry, healthcare and governance. This journal explores their interdependence, assesses their current and potential roles, and identifies challenges and opportunities. Through critical analysis, this study offers suggestions for enhancing digital literacy and ensuring ethical and inclusive integration of technology